Implementation of Simple Additive Weighting to Decide a Fund Proposal - Rakhmadi, Aris; Rahmawati, Nila Dwi (Emerging Information Science and Technology, 2023)
One of Indonesian micro financial services is Baitul Maal Wat Tamwil (BMT) provides services such as savings, financing and zakat activities. Financing service determine qualifying status based on consideration of customer files before carried out in company discussions. This decision support system aims to provide officers to decide whether or not to admit funding. The research used Simple Additive Weighting (SAW) by finding the prejudiced sum of the performance ratings for each alternative from all criteria. The method used 7 criteria including income, outstanding loans, amount of financing, collateral, nature/environment, track record of financing and monthly expenses. Customers were declared acceptable if they had a preference value above the minimum limit of 16.1. The BMT officer can adjust the minimum limit value according to customer performance. To develop the system used waterfall method and to verify system performance used a black box test which shows the results that the system works according to its function and the validity test results obtained 100% accurate. It means the system is ready and suitable for use. The existence of this decision support system is able to assist officers in making decisions to qualify for financing objectively.